Investigation of the influence of the mode of heat treatment of the initialpowder on the efficiency of sintering zirconium ceramics by dilatometry; Вестник Карагандинского университета. Серия Физика; № 3 (103) - Shevelev S. A. Sergey Anatolievich (2021, 2021)
Using methods of synchronous thermal and X-ray structural analyzes applied to zirconium dioxide powders partially stabilized with yttrium obtained by chemical coprecipitation the processes of dehydration of these powders during annealing in air have been investigated. Using the dilatometry method, the regularities ofcompaction of powder compacts have been investigated with thermal sintering. It was found that the resulting powders mainly consist of the tetragonal modification zirconium dioxide and are nano-sized. The average particle size was 25 nm. The resulting powders are characterized by a high degree of agglomeration. It isshown that an increase in the thermal annealing temperature from 500 to 700є? leads to partial baking of individual particles inside the agglomerate, and causes the formation of hard agglomerates, the presence of which complicates the processes of compaction and subsequent sintering. The presence of such agglomerates prevents the production of ceramics with high mechanical characteristics: density and porosity. Thermal annealing temperature increase leads to a decrease in the density of the sintered ceramic and a decrease in its hardness.